2016
DOI: 10.1002/ejoc.201601239
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Synthesis of a Known Intermediate in the Formal Synthesis of (–)‐Steganacin

Abstract: The formal synthesis of the two enantiomers of a natural, axially chiral biaryl, steganacin, is reported. The previously developed atropo‐diastereoselective coupling of an aryne and an aryllithium (“aryne coupling”) allows for this synthesis. In each step, the axial configuration of the biaryl could be maintained. The key intermediate, identified previously, was accessed without using transition metals, which demonstrates the potential of the aryne coupling reaction as a complementary or alternative to transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…On the other hand, employing 2 equiv of the bulkier t -BuLi instead of 1 equiv of BuLi only afforded the starting material. This result is coherent with related findings by our group in the case of a hindered iodine atom ortho to the aryl–aryl bond …”
Section: Resultssupporting
confidence: 94%
“…On the other hand, employing 2 equiv of the bulkier t -BuLi instead of 1 equiv of BuLi only afforded the starting material. This result is coherent with related findings by our group in the case of a hindered iodine atom ortho to the aryl–aryl bond …”
Section: Resultssupporting
confidence: 94%
“…In this context, Leroux et al reported an efficient transition metal free aryl‐aryl coupling protocol, the so‐called “Aryne coupling” reaction . Very recently, we extended the reaction to the construction of hetaryl‐aryl backbones, developing thus the “(Het)‐Aryne” version of the reaction (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Leroux et al reported an efficient transition metal free aryl-aryl coupling protocol, the so-called "Aryne coupling" reaction. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Very recently, we extended the reaction to the construction of hetaryl-aryl backbones, developing thus the "(Het)-Aryne" version of the reaction (Scheme 1). [44] However, our study essentially focused on the thiophene ring as a model partner.…”
Section: Introductionmentioning
confidence: 99%